Public procurement legislation in Bangladesh: a study on the application of PPA, 2006 and PPR, 2008 in the procurement activities of Election Commission Secretariat - Ahsan, Md. Rajib (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2023.